The Effect of Ethical Advertising Practices on the Financial Performance of Listed Firms in the Nairobi Securities Exchange (NSE) - Ogwoka, Manduku Daniel; Namada, Juliana; Sikalieh, Damary (European Journal of Business and Strategic Management, 2017)
ntroduction: Listed firms in the Nairobi Securities Exchange have consecutively witnessed deteriorating financial performance over the last five years. Among the various hypothetical precursory factors that can be linked to that decline, the ethical inclination of the human advertisement practices is critical. Purpose: The objective of this study was to determine the influence of Ethical Advertisement practices on the financial performance of the listed firms. Methodology: The study adopted a census method of research involving all the listed firms. Structured questionnaires were used as the data collection tool. Findings: The results established that ethical advertising practices have a positive impact on financial performance. Contribution: The study findings indicated that financial performance was high when firms adhered to ethical advertising, when advertisements satisfied customer requirements and when the firms employed ethical practices for their products. The study therefore recommends that firms need to ensure that there is adherence to ethical advertising, they satisfy their customer requirements and employ ethical advertising practices for their products. The study also recommends that listed firms should fully harness the use of internet services during advertising to help them accomplish quick developments, versatility, productivity, and thus, positive financial returns